Semiconductor Gas Sensors: Metal Oxides, Synthesis Methods, Applications as Gas Sensors, and Oxidation and Reduction Mechanisms - Hammod, Inam Abed; Ridha, Noor Jawad; Tahir, Khawla Jemeel; Alosfur, Firas Kamel Mohamad; Yasir, Asaad Sabbar; Majeed, Luma Ahmed (Universitas Gadjah Mada, 2025)
Over the last several decades, advancements in industry have facilitated the absorption of harmful gases into the bloodstream or lungs via dermal absorption or inhalation. This process may elicit diverse cellular responses, potentially leading to adverse health effects. Consequently, air pollution has emerged as a significant worldwide issue. Hence, developing a device capable of monitoring air pollution and detecting these chemicals in the surrounding environment became imperative. Gas sensors are instruments used for regulating industrial emissions, surveillance of environmental contaminants, and identification of pollutants and hazardous gases. Semiconductor gas sensors have garnered significant recognition owing to their several advantageous characteristics, including simplified production processes, compact dimensions, and low-cost. Some of its drawbacks include limited selectivity and high operating temperatures. This review discusses the most often used semiconducting materials in gas sensing, as well as the methods used to synthesize them, and the reduction and oxidation processes that happen between metal oxides and analyte gas. Furthermore, the various strategies employed to increase the gas-sensing response are explored, such as doping with noble metals and the formation of heterostructures.